The coronavirus conundrum, the pregnant woman, her child. Part 2 - Pacheco-Romero, José (2020)
When COVID-19 appeared, we did not expect its rapid expansion throughout the world nor the serious consequences it would bring. We currently understand more about the virus’ morphology and its activity in the environment and within the human body, as well as its greater predisposition to affect vulnerable populations, such as the elderly and persons with comorbidities like obesity, diabetes, hypertension and immunosuppression. This virus shows a predilection for men, and a higher prevalence in countries with greater poverty, promiscuity and economically depressed areas, among others. Various treatments have been tested and discarded in patients with moderate and severe disease. The frequency of deaths is decreasing due to personal protection measures, social distancing, emergency quarantine, and combination of medications and supplemental oxygen. However, there is still no cure, and we are waiting for the appearance of the vaccine. Women are less frequently and less severely affected; however, they should follow preventive measures, especially if frail with comorbidities. Preventive medical consultations and non-emergency surgical procedures have been temporarily postponed. Pregnant women are experiencing an increase in prematurity, fetal deaths, placental lesions and presence of the virus in placental adnexa, with cases of severe morbidity and maternal death. This article is an update on the situation of COVID-19 in the world and in Peru, emphasizing the care of women and pregnant women.